The Influence of Celebrity Worship On Celebrity Endorsement Towards Purchase Decisions In West Java (Case Study Blackpink At Tokopedia) - Nofifa Anggraeni; Rendika Nugraha (FIRM Journal of Management Studies, 2022)
This research investigates the influence of Celebrity Endorsement towards Purchase Decisions by bringing up celebrity worship behaviors. This research raised the Blackpink endorsement program at Tokopedia as the study case. Quantitative method used in this study to analyze the data using Structural Equation Model analysis. The questionnaire was distributed by using Google Form and spread to West Java as the targeted respondents. The sample size of this study is 581 respondents who are following and like Blackpink and use Tokopedia. This research was analyzed through Smart-PLS 3.0. This Researxh found that Celebrity worship as the Independent variable becomes the factor to influence Celebrity Endorsement. The result showed Celebrity endorsement is significantly influenced Purchase Decisions and Brand Awareness. As the first study that combines purchase decisions and celebrity worship variables in the construct. This research uses Blackpink's endorsement on Tokopedia as a study case.